OSRA Grant Cycle 1 Public Reports : Project Title: Parenting Style Influences on Child Academic Achievement and University Adjustment - Said Aldhafri (16140251) (2019)
This longitudinal study in the GCC region investigated the effects of students' perceptions of parenting styles on their academic performance and social adaptability. Employing a year-long research design, the project involved 2267 grade-twelve Omani students in two phases. The first phase revealed significant correlations between various parenting styles and academic achievement, with mother's parenting styles emerging as key predictors, explaining 8% of the variance. The second phase focused on university adjustment and found that parenting styles, particularly permissive mothers and authoritative fathers, significantly influenced academic adaptation, explaining 7.5% of the variance, while not predicting social and psychological adjustment. These findings underscore the potential for enhancing counseling services to support students with parenting-related concerns in higher grades and their initial college year, while also highlighting the role of personal and institutional factors in university experiences.